Defect dynamics in the presence of excess energetic carriers and high electric fields in wide-gap semiconductors - O’Hara, Andrew; Schrimpf, Ronald D.; Fleetwood, Daniel M.; Pantelides, Sokrates T. (Journal of applied physics, 2024)
Irradiation of semiconductors by energetic beams generates excess electrons and holes and may cause device degradation or failure. Both gradual degradation by total ionizing radiation (TID) and sudden degradation/failure (soft/hard breakdown) by a combination of energetic heavy ions and high voltages (typically single-event effects or SEEs) are mediated by excess carriers. The role of defect dynamics in TID degradation has been adequately understood by a combination of experiments and density-functional-theory (DFT) quantum calculations, but little has been done so far to document a role for ion-induced defects in SEE. Here, we report proof-of-principle DFT calculations in a model cubic GaN system for two defect-related excess-carrier phenomena that can play a role in various forms of device degradation and failure. The first phenomenon is the existence, dynamics, and potential roles of defect-induced quasi-localized “resonant states” in the energy-band continua. These states can enhance TID-excess-carrier and hot-carrier degradation. Furthermore, they evolve and multiply during energetic-ion-induced atom recoils and defect creation (displacement damage) and can potentially serve as excess-carrier conduction paths in SEE. The second phenomenon is the conversion of isolated vacancies into nanovoids that can participate in the formation of conducting defect “nanowires” dressed by resonances or in explosive SEE hard breakdowns.